Calcium Imaging Analysis of Cellular Responses to Hypercapnia and Hypoxia in the NTS of Newborn Rat Brainstem Preparation - Onimaru, Hiroshi; Yazawa, Itaru; Takeda, Kotaro; Fukushi, Isato; Okada, Yasumasa (Frontiers in Physiology, 2021)
It is supposed that the nucleus of the solitary tract (NTS) in the dorsal medulla includes gas sensor cells responsive to hypercapnia or hypoxia in the central nervous system. In the present study, we analyzed cellular responses to hypercapnia and hypoxia in the NTS region of newborn rat in vitro preparation. The brainstem and spinal cord were isolated from newborn rat (P0-P4) and were transversely cut at the level of the rostral area postrema. To detect cellular responses, calcium indicator Oregon Green was pressure-injected into the NTS just beneath the cut surface of either the caudal or rostral block of the medulla, and the preparation was superfused with artificial cerebrospinal fluid (25–26°C). We examined cellular responses initially to hypercapnic stimulation (to 8% CO2 from 2% CO2) and then to hypoxic stimulation (to 0% O2 from 95% O2 at 5% CO2). We tested these responses in standard solution and in two different synapse blockade solutions: (1) cocktail blockers solution including bicuculline, strychnine, NBQX and MK-801 or (2) TTX solution. At the end of the experiments, the superfusate potassium concentration was lowered to 0.2 from 3 mM to classify recorded cells into neurons and astrocytes. Excitation of cells was detected as changes of fluorescence intensity with a confocal calcium imaging system. In the synaptic blockade solutions (cocktail or TTX solution), 7.6 and 8% of the NTS cells responded to hypercapnic and hypoxic stimulation, respectively, and approximately 2% of them responded to both stimulations. Some of these cells responded to low K+, and they were classified into astrocytes comprising 43% hypercapnia-sensitive cells, 56% hypoxia-sensitive cells and 54% of both stimulation-sensitive cells. Of note, 49% of the putative astrocytes identified by low K+ stimulation were sensitive to hypercapnia, hypoxia or both. In the presence of a glia preferential blocker, 5 mM fluoroacetate (plus 0.5 μM TTX), the percentage of hypoxia-sensitive cells was significantly reduced compared to those of all other conditions. This is the first study to reveal that the NTS includes hypercapnia and hypoxia dual-sensitive cells. These results suggest that astrocytes in the NTS region could act as a central gas sensor.